EVALUASI INISIATIF BLUE DIGITAL PERUSAHAAN KELAUTAN DAN PERIKANAN DI INDONESIA - Richard Andrew; Yosef Pranata (ICMA Nasional, 2026)
This paper examined the role of Blue Accounting digital as an innovative mechanism to simultaneously address poverty alleviation and environmental sustainability. The study applied a conceptual research approach supported by content analysis of sustainability disclosure practices in the marine and fisheries sector in Indonesia. The analysis focused on dimensions such as community involvement, resource efficiency, emission reduction, biodiversity protection, and economic inclusion. The results showed that companies implementing comprehensive Blue Accounting practices, particularly in line with sustainability reporting standards, demonstrated higher transparency, stronger environmental stewardship, and better integration with local community livelihoods. In particular, Blue Accounting contributed to poverty alleviation by strengthening partnerships with small-scale fishers and ensuring fair access to supply chains, while also contributing to environmental sustainability through improved monitoring of emissions, biodiversity, and ecosystem conservation. The findings emphasized that Blue Accounting could serve as a strategic innovation that aligns with the Sustainable Development Goals. This study contributed to the development of sustainability accounting frameworks and offered practical implications for policymakers, corporations, and civil society to integrate environmental accountability with social inclusion for resilient blue economies